Concentración bancaria, competencia y estabilidad financiera en Colombia (2019)
The recent increase in concentration levels and the regulation of financial systems around the world has revived the debate on the relationship between banking concentration, market competition and financial stability. In this paper, we study the relationship between these variables for the recent Colombian case. Our results confirms the existence of a strong banking concentration process during the last decade, which has been accompanied in turn by a decrease in the level of competition among banks. However, this process has not compromised the stability of the banking system. On the contrary, it has been improved. Finally, we found a non-linear relationship between these variables, suggesting it is not recommended to increase the banking concentration levels in to the future.